Emotional dysregulation in childhood and disordered eating and self‐harm in adolescence: prospective associations and mediating pathways. (21st December 2022) - Warne, Naomi; Heron, Jon; Mars, Becky; Solmi, Francesca; Biddle, Lucy; Gunnell, David; Hammerton, Gemma; Moran, Paul; Munafò, Marcus; Penton‐Voak, Ian; Skinner, Andy; Stewart, Anne; et al.
Abstract : Background: Emotional dysregulation may be a risk factor for disordered eating and self‐harm in young people, but few prospective studies have assessed these associations long‐term, or considered potential mediators. We examined prospective relationships between childhood emotional dysregulation and disordered eating and self‐harm in adolescence; and social cognition, emotional recognition, and being bullied as mediators. Methods: We analysed Avon Longitudinal Study of Parents and Children data on 3, 453 males and 3, 481 females. We examined associations between emotional dysregulation at 7 years and any disordered eating and any self‐harm at 16 years with probit regression models. We also assessed whether social cognition (7 years), emotional recognition (8 years) and bullying victimisation (11 years) mediated these relationships. Results: Emotional dysregulation at age 7 years was associated with disordered eating [fully adjusted probit B (95% CI) = 0.082 (0.029, 0.134)] and self‐harm [fully adjusted probit B (95% CI) = 0.093 (0.036, 0.150)] at age 16 years. There was no evidence of sex interactions or difference in effects between self‐harm and disordered eating. Mediation models found social cognition was a key pathway to disordered eating (females 51.2%; males 27.0% of total effect) and self‐harm (females 15.7%; males 10.8% of total effect). Bullying victimisation was an important pathway to disordered eating (females 17.1%; males 10.0% of total effect), but only to self‐harm in females (15.7% of total effect). Indirect effects were stronger for disordered eating than self‐harm. Conclusions: In males and females, emotional dysregulation in early childhood is associated with disordered eating and self‐harm in adolescence and may be a useful target for prevention and treatment. Mediating pathways appeared to differ by sex and outcome, but social cognition was a key mediating pathway for both disordered eating and self‐harm.